Teacher Instructional Strategies and Student Learning Interest in Senior High School Classrooms: Evidence from an Ex Post Facto Study - Jusnia; Emmi Azis; Sahiruddin (Yayasan Ahmar Cendekia Indonesia, 2026)
This study examines the relationship between teacher instructional strategies and student learning interest in senior high school classrooms. A quantitative ex post facto design was employed involving 32 tenth-grade students selected through purposive sampling. Data were collected using Likert-scale questionnaires measuring teacher instructional strategies and student learning interest, supported by school documentation. The data were analyzed using descriptive statistics, normality and linearity tests, simple linear regression, and partial significance testing. The descriptive findings indicate that both teacher instructional strategies and student learning interest were categorized at high levels. Regression analysis produced the equation Y = 26.048 + 0.369X, with a significance value of 0.005, indicating a statistically significant positive relationship between the two variables. These findings suggest that students tend to demonstrate stronger interest in learning when teachers employ more varied, engaging, and student-centered instructional strategies. The study highlights the importance of instructional strategy selection in creating learning environments that sustain student attention, participation, and interest. The findings also provide practical implications for teachers seeking to improve classroom engagement through more adaptive and responsive instructional practices.